2019
DOI: 10.1007/s42452-019-0349-z
|View full text |Cite
|
Sign up to set email alerts
|

3D spongy-like Au film for highly stable solid contact potentiometric ion selective electrode: application to drug analysis

Abstract: Potentiometric ion selective electrodes with simple design and high potential stability are required for in-line process, clinical and quality control analysis. The objective of this work is to develop a high-surface-area Au nanostructure solidcontact (SC) platform for high stable ion selective electrode for drug analysis. Memantine, a pharmaceutical compound prescribed for Alzheimer's disease, with challenging measurable analytical characteristics, was selected as a model for this purpose. Internal solid-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Pt solid contact electrdoe was prepared as described previously [ 55 ]. In brief, the electrode was cleaned using alumina paste of 15, 3 and 1 µm and then rinsed with deionized water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pt solid contact electrdoe was prepared as described previously [ 55 ]. In brief, the electrode was cleaned using alumina paste of 15, 3 and 1 µm and then rinsed with deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…This Nanomaterial provides high surface area, high conductivity as well as the ability to function as an ion-to-electron transducer when used as an electron conductors in SC-ISEs [ 54 ]. Solid contact potentiometric ISEs with metal nanoparticles have also been reported for determination of K + [ 45 ] and pharmaceutical compounds [ 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…[134][135][136] Nanoporous metal materials have attracted considerable interest for the development of SC-ISEs due to their numerous interconnected nano-sized cavities that can provide a large area for ion interaction and adsorption. [137][138][139] For example, nanoporous gold film and platinum oxide were used widely as the solid contact in ISEs, which demonstrated high potential stability with a short response time. [140][141][142] The impact of different types of metal oxide nanoparticles as the solid contact, including zinc oxides, iron oxides, and copper oxides, on the sensing performance of ISEs for K + detection was studied by Wardak et al 120 It was found that the integration of metal oxide nanoparticles into the electrode enhanced its performance, particularly in terms of electrical parameters and potential stability; this could be attributed to excellent electrochemical activity and a high surface-to-volume ratio.…”
Section: Metal-based Nanomaterialsmentioning
confidence: 99%
“…The electrodes have the advantages of small size, easy construction and can be used in different space position with easy rotation and vibration. They have no inner filling solution where the ion selective membrane is in direct contact with the solid transducer surface [16,17]. Recently, mass production of inexpensive, portable and reliable all-solid-state electrodes for environmental and pharmaceutical analysis has attracted great attention [18].…”
Section: Introductionmentioning
confidence: 99%